Geothermics - DECDFI (My University, 1976)
This Algerian locality, well know for its thermal sours and the concretions which these sources have produced, well furnish us with a remarkable illustration of the stabilization of a conduit by convection. A small plain is found there having hundreds of limestone formations of about the same height (around 3 m). Each of these formations corresponds to a thermal conduit from which emerged at a temperature near 100°C and has produced abundant concretions, raising the conduit up to a height, it ceases to function and another conduit develops next to it. When the conduit in functioning, its walls are heated and the entire water column is at 100°C for which the specific volume of water is 1.0434.
Keywords: geothermics; management; enviromental; development; survey